Severe Penile Curvature following Otis Urethrotomy. (25th March 2013) - Karaguzel, Ersagun; Gur, Metin; Tok, Dogan S.; Kazaz, İlke O.; Eren, Huseyin; Kutlu, Omer; Ozgur, Guner K.
Abstract : Urethral stricture is a common urological pathology with a high recurrence rate after treatment. Urethral manipulations are among its main causes. In this paper, urethral stricture developed secondary to urethral catheterization and was treated with cold-knife internal urethrotomy and the Otis urethrotomy procedure. During the follow-up period, severe ventral penile curvature preventing sexual intercourse developed due to fibrosis of the corpus spongiosum and tunica albuginea of the penis. This ventral penile curvature was corrected with a separate operation using a tunica vaginalis flap harvested from the left scrotum.